2021
DOI: 10.1177/02692155211012004
|View full text |Cite
|
Sign up to set email alerts
|

Interferential current and photobiomodulation in knee osteoarthritis: A randomized, placebo-controlled, double-blind clinical trial

Abstract: Objectives: To evaluate the effects of interferential current and photobiomodulation in patients with knee osteoarthritis. Design: A randomized, placebo-controlled, double-blind clinical trial. Setting: Physiotherapy Clinic of City University of São Paulo. Subjects: A total of 184 patients with knee osteoarthritis were recruited and, of these, 168 were included and randomized into four groups with 42 each: interferential current, photobiomodulation, interferential current plus photobiomodulation or placebo gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…After reviewing the remaining articles’ titles and full texts, 67 articles were identified as irrelevant articles and were excluded. Among the remaining 33 articles, 10 RCTs met the eligibility criteria 16 – 25 , and nine RCTs 17 25 were pooled into our meta-analysis; they were all parallel studies. A detailed flowchart of the study selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After reviewing the remaining articles’ titles and full texts, 67 articles were identified as irrelevant articles and were excluded. Among the remaining 33 articles, 10 RCTs met the eligibility criteria 16 – 25 , and nine RCTs 17 25 were pooled into our meta-analysis; they were all parallel studies. A detailed flowchart of the study selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nine trials 17 25 reported improvement of pain as a main outcome by using the visual analog scale (VAS) or the numeric rating scale (NRS) 26 . For the assessment of functional capacity, seven trials 18 , 20 25 used the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), which assesses the domains of pain, joint stiffness, and physical activity 27 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations